Social Consequences of Admitting Crime on Prisoner’s Life - Suren AkramHamanajm (QALAAI ZANIST JOURNAL, 2023)
This research has two gates, the first gate is dedicated to the theory of the research and it has three chapters. In chapter one, the (problem, significance, and purpose) of the research has been written. In chapter two the concepts of (Consequence, crime, and presence) has been defined .in chapter three labeling theory and victimology has been clarified. The second gate has been dedicated for applied research; chapter four is dedicated for (research community, sample of research, the method of the research, Tools for Gathering Information). Chapter five is about Analysis and Presentation Data, first debate showsAnalysis and PresentationData, Second debate determinations Conclusion, Research results, Research recommendations Research suggestions, Bibliography.